IMMIGRANT NEIGHBORHOODS IN CHICAGO AND COMMUNITY SCHOOLS: A MODEL FOR STUDENT SUCCESS - Carlos M. Azcoitia (European Scientific Journal, ESJ, 2015)
Schools can become the focus of community connected to daily lives and experiences. They can also address the academic and social context of education with strategic partnerships. Educational experiences are affected by school and non-school factors; therefore, schools need to expand their boundaries to other areas which affect learning. The greatest influence on students is the family and the greatest influence on families is the community so schools need to seek the integration of school, family and community to deliver a quality educational program for all students. Supporting and challenging students entail supporting and strengthening families. There is interdependence among schools, families and communities in order to exert a positive influence on academic outcomes. This paper examines the characteristics of effective community schools in a study of one particular school in an immigrant neighborhood in Chicago.